Interaksi Asam Galat dan Metil Galat dari Tumbuhan Kasturi (Mangifera casturi) sebagai Inhibitor Protein Human Epidermal Growth Factor 2 (HER2): Evaluasi Molekular Docking - NOER KOMARI; ROBIATUL ADAWIYAH; SAMSUL HADI; EKO SUHARTONO (UIN Sunan Gunung Djati Bandung, 2022)
Kasturi (Mangifera casturi) is a endemic plant of Borneo. The polyphenol content of M. casturi leaves has antioxidant properties, including gallic acid and methyl gallic. The antioxidant potential of gallic acid and methyl gallate of M. casturi leaves is thought to inhibit the growth of breast cancer cells. Human Epidermal Growth Factor 2 (HER-2) protein is an important factor in the epidermal growth of breast cells and is also a target for breast cancer treatment. This study aims to investigate the potential of gallic acid and methyl gallic compounds from M. casturi as inhibitors of HER-2 protein. Molecular docking parameters in Gibbs free energy, interaction of gallic acid and methyl gallic ligands with HER-2 protein residues Kasturi (Mangifera casturi) is a endemic plant of Borneo. The polyphenol content of M. casturi leaves has antioxidant properties, including gallic acid and methyl gallic. The antioxidant potential of gallic acid and methyl gallate of M. casturi leaves is thought to inhibit the growth of breast cancer cells. Human Epidermal Growth Factor 2 (HER-2) protein is an important factor in the epidermal growth of breast cells and is also a target for breast cancer treatment. This study aims to investigate the potential of gallic acid and methyl gallic compounds from M. casturi as inhibitors of HER-2 protein. Molecular docking parameters in Gibbs free energy, interaction of gallic acid and methyl gallic ligands with HER-2 protein residues